Gender and the “Membership in a Particular Social Group” Category of the 1951 Refugee Convention - Binder, Andrea (Columbia Journal of Gender and Law, 2001)
The criteria of “membership in a particular social group,” as laid down in the U.N. Convention Relating to the Status of Refugees, and codified in the Refugee Act of 1980, is an element of the universally recognized refugee definition which has become a critical point for many women seeking asylum in the United States and elsewhere. A person seeking refugee recognition not only has to demonstrate that she has been persecuted or has a “well-founded” fear of persecution; in addition, she must show that the persecution directed against her is caused by a discriminatory motive as stated in the refugee definition. Such grounds for persecution are limited to race, religion, nationality, political opinion, or membership in a particular social group. Women are persecuted for the same reasons as men; for example, they are arrested and tortured due to their publicly demonstrated political opinions. However, women frequently face gender-based persecution, which may have two different meanings: “The concept of women being persecuted as women is not the same as women being persecuted because they are women.” The first concept, that of women persecuted as women, relates to the types and forms of persecution that are gender-specific, such as rape, female genital mutilation (FGM), or domestic abuse. The second concept, that of women persecuted because they are women, addresses the causal relationship between gender and persecution. The term gender- related persecution refers to the latter and focuses on the bases of persecution. Gender alone, or combined with other characteristics, can be the basis for the persecution. This two-pronged definition of gender-based persecution illustrates that gender-specific harm is not necessarily persecution perpetrated because of the victim’s gender. As the case of female genital mutilation shows, a woman (or girl) may be persecuted both as and because she is a woman (or girl).